Serum pepsinogen and gastrin‑17 as potential biomarkers for pre‑malignant lesions in the gastric corpus - Loong T.H.; Soon N.C.; Nik Mahmud N.R.K.; Naidu J.; Abdul Rani R.; Hikmah Elias M.; Rose I.M.; Tamil A.; Mokhtar N.M.; Raja Ali R.A.; Nazefah Abdul Hamid (Spandidos Publications, 2024)
Abstract. There is a lack of non‑invasive screening modalities to diagnose chronic atrophic gastritis (CAG) and intestinal metaplasia (IM). Thus, the aim of the present study was to determine the sensitivity and specificity of serum pepsinogen I (PGI), PGI:II, the PGI:II ratio and gastrin‑17 (G‑17) in diagnosing CAG and IM, and the correlations between these serum biomarkers and pre‑malignant gastric lesions. A cross‑sectional study of 72 patients (82% of the calculated sample size) who underwent oesophageal‑gastro‑duodenos-copy for dyspepsia was performed in the present study. The mean age of the participants was 56.2±16.2 years. Serum PGI:I, PGI:II, G‑17 and Helicobacter pylori antibody levels were measured by enzyme‑linked immunosorbent assay. Median levels of PGI:I, PGI:II, the PGI:II ratio and G‑17 for were 129.9 µg/l, 10.3 µg/l, 14.7 and 4.4 pmol/l, respectively. Subjects with corpus CAG/IM exhibited a significantly lower PGI:II ratio (7.2) compared with the control group (15.7; P<0.001). Histological CAG and IM correlated well with the serum PGI:II ratio (r=‑0.417; P<0.001). The cut‑off value of the PGI:II ratio of ≤10.0 demonstrated high sensitivity (83.3%), specificity (77.9%) and area under the receiver operating characteristic curve of 0.902 in detecting the two conditions. However, the sensitivity was particularly low at a ratio of ≤3.0. The serum PGI:II ratio is a sensitive and specific marker to diagnose corpus CAG/IM, but at a high cut‑off value. This ratio may potentially be used as an outpatient, non‑invasive biomarker for detecting corpus CAG/IM.